Atividade antimicrobiana in vitro de extrato de Punica granatum L. sobre staphylococcus aureus isolado em leite bovino - Silva, Bruno Toledo; dos Anjos, Carolina; Novo, Sylvia Marquart Fontes; Matsumoto, Leopoldo Sussumu; Peixoto, Erika Cosendey Toledo de Mello; Silva, Luciana Pereira [UNESP]; Silva, Regildo Márcio Gonçalves da [UNESP] (My University, 2013)
Bovine mastitis is considered important disease causing major economic losses in dairy herds. Antimicrobial drug can promote resistance, chemical residues in food and environmental contamination. The purpose of this study was to evaluate the antibacterial activity in vitro of pomegranate extract on Staphylococcus aureus isolated from bovine milk, evaluate its antioxidant activity, and quantify levels of total phenols and fravonoides of the different extracts used. Aqueous extracts were used in nature and dry, from the peel of the fruit (EAC) and leaves (EAF). Additionally, it was evaluated the antioxidant activity (AA%), total phenols and flavonoids. Milk samples were inoculated, incubated, and the colonies were characterized as Staphylococcus aureus were adjusted to 1.0x106 UFC/mL in the 6 standard of the MacFarland scale. The sensitivity of the microbial isolates were determined in quintuplicate, in disk diffusion test. The minimum inhibitory concentration was determined by visible inhibition zone greater than 15mm. The results were evaluated by ANOVA, Tukey 5%, using the program SISVAR 5.3 - DEX/UFLA. Results implied that the aqueous extract from the bark of dried fruit was capable of inhibiting bacterial growth at concentrations of 3%. The other treatments only showed this activity, from the concentrations of 15%, 20% and 30% for dry EAF, in nature EAC and in nature EAF, respectively. Regarding the action antioxidant of dry EAC, was not correlated with total phenols and flavonoids. Probably other alkaloids substances present in the extract studied, may have been responsible for this activity. It is concluded that extracts of Punica granatum L., especially those obtained by the shell of the fruit, showed inhibitory activity against S. aureus, indicating your use potential for the control of bovine mastitis.

Mastite bovina é considerada principal doença causadora de grandes perdas econômicas nos rebanhos leiteiros. Antimicrobianos químicos promovem resistência farmacológica, resíduos no alimento e contaminação ambiental. Este estudo objetivou verificar a atividade antibacteriana, in vitro, do extrato de romã em Staphylococcus aureus isolado de leite bovino, avaliar sua atividade antioxidante, e quantificar teores de fenóis e flavonoides totais nos diferentes extratos utilizados. Utilizou-se para tanto extratos aquosos da casca do fruto (EAC) e folhas (EAF), secos e in natura de romã. Adicionalmente, avaliou-se atividade antioxidante (AA%), teores de fenóis e flavonóides totais. Amostras de leite foram semeadas, incubadas, e as colônias de Staphylococcus aureus foram ajustadas a 1,0x106 UFC/mL ao padrão nº6 da escala de MacFarland. A sensibilidade dos isolados microbianos foi determinada, em quintuplicata, pela técnica de difusão em discos. A Concentração Inibitória Mínima foi determinada pelo halo de inibição superior a 15 mm. Os resultados foram avaliados pelo método ANOVA, teste de Tukey 5%, utilizando-se o programa SISVAR 5.3 - DEX/UFLA. EACseco inibiu crescimento bacteriano a partir de 3%. EAFseco, EACin natura e EAFin natura, só apresentaram esta atividade a partir de 15%, 20% e 30% respectivamente. A ação antioxidante do EACseco foi verificada a partir de 75µg/mL, com valores correspondentes a 14,2%, atingindo um platô de 65,9% na concentração de 250µg/mL. Entretanto, essa atividade não foi correlacionada aos teores de fenóis totais e flavonoides. Provavelmente outras substâncias alcalóides, podem ter sido responsáveis por esta atividade. Conclui-se que os extratos de Punica granatum L., principalmente aquele obtido pela casca do fruto seco, demonstraram atividade inibitória sobre S. aureus, evidenciando a potencialidade de seu uso para o controle da mastite bovina.
Antimicrobial activity in vitro of extracts of Punica granatum L. over staphylococcus aureus isolated in bovine milk
Keywords: Agroecology; Antibacterial; Biodinamic production; Mastitis; Organic animal production